Analysis of the results of the pedagogical experiment on implementing the pedagogical technology of forming future agrarians’ multicultural competence - Kravets, Ruslan (ScienceRise: Pedagogical Education, 2017)
The authorial pedagogical technology of forming the multicultural competence of future agrarians has been checked. The modified conditions of the research work include the methodology of interrelated teaching a foreign language and a culture. The English language played the role of the means of multicultural interaction among the representatives of different countries and the tool of effective professionally development. The pedagogical process has been organized on the basis of the personality orientated, communicative, axiology and linguistic regional geography approaches. Professionally-oriented foreign and multicultural materials have been used. In choosing the teaching methods we have considered the academic peculiarities of students-agrarians, based on the specific principles of future agrarians’ multicultural education at foreign language classes: the principle of the dialogue of cultures, the principle of cultural suitability, the principle of national and common humanity unity, the principle of multiculturalism and multicultural tolerance, the principle of problem culture-regional tasks prevailing, the principle of authenticity, the principle of novelty, the principle of professional orientation. It has been proved experimentally, that forming of the multicultural competence will be successful in case of observing the following pedagogical conditions: implementing the interactive teaching methods for increasing the internal motivation of educational activity; the organization of the educational multicultural environment as the social system of a multi-subject type at the agrarian higher educational institution; rational combining classroom and independent work; application of electronic educationally-methodological complex of forming future agrarians’ multicultural competence